DELIVERY OF MUMMIFIED FETUS BY CAESAREAN OPERATION IN AN ONGOLE COW - RAO, M MUTHA; SREENU, M; PANDEY, A K (The Indian Journal of Animal Reproduction, 2023)
A case of fetal mummification resolved by Caesarean operation in a pluriparous Ongole cow was reported and discussed.
Keywords: Mummification; Caesarean operation; Ongole cow